Controle e automação das medidas de um eletrômetro acoplado a um detector de radiação, usando microcontrolador Pic e linguagem Assembly - Abner Pinto da Fonseca (2013)
This work had as main objective the automation of electrical charge generated measures within a radiation detector, i.e., an automated device was developed for data acquisition. These measurements are performed by an electrometer and allow the determination of the dose and/or dose rate due to a radioactive source at various distances source-detector. It also allow the calibration of detectors with greater precision, simulating an infinite source and verification of sources homogeneity. The above said automated device is supported by a mechanical structure comprising two tables moving orthogonally and each of them are driven by a stepping motor. The system has two directions of displacement, a call X (cartesian axis X) with freedom of movement -20.0 cm to 20.0 cm and 1.0 cm steps, while the other called the Y direction (axis Y) moves from 2.0 to 92.0 cm, and also 1.0 cm steps. For each direction it was built a table which supports a tower. The Y tower carries a radiation detector, ionization chamber, whose window remains inline on the Y axis and X tower carries the radioactive source. Upon the X tower it was settled another stepper motor that adjusts the direction of radiative beam towards the geometric center of the detector. At each increment of 1.0 cm in X and Y, totaling 3,731 positions, the electrometer performs the measurement of electrical charge generated inside an ionization chamber in an automated form. These measures are read by a microcontroller (PIC16F877A, programmed in assembly language) and stored in a serial memory Electrically Erasable Programmable Read- Only Memory (EEPROM), both residing in a Printed Circuit Board (PCB) that was built for this project.Finalized the process of measuring the stored values should be transmitted to a personal computer, in text mode, and transferred to a spreadsheet to be worked out statistically to determine the dose rate and absorbed dose.